Neutrophil percentage-to-albumin ratio as a novel hematologic biomarker for predicting arteriogenic erectile dysfunction - Mei, Yangyang; Zhang, Guoyang; Liu, Yu; Chen, Yiming; Xu, Renfang; Lu, Hao; Gao, Hui; Sun, Xianchao; Zhang, Wei; Feng, Xingliang; Zhuang, Qianfeng (Frontiers in Endocrinology, 2026)
BackgroundThe neutrophil percentage-to-albumin ratio (NPAR) is a novel composite marker reflecting both inflammatory and nutritional status. However, its association with arteriogenic erectile dysfunction (AED) has not been previously investigated. This study aimed to evaluate the relationship between NPAR and AED and to determine its diagnostic performance compared with conventional hematologic parameters.MethodsA total of 265 men were enrolled from three hospitals between April 2023 and August 2025, including 115 with AED, 53 with venogenic ED (VED), and 97 healthy controls. Erectile function was assessed by the five-item International Index of Erectile Function (IIEF-5), nocturnal penile tumescence and rigidity (NPTR) test and color duplex Doppler ultrasonography (CDDU) was used to classify ED subtypes. Laboratory parameters, including white blood cell (WBC) count, neutrophil percentage (NP), albumin, and NPAR, were measured. Group differences were analyzed using ANOVA or the Kruskal–Wallis test, and independent predictors of AED were identified using multivariate logistic regression. Diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis. Subgroup analyses were conducted to assess robustness.ResultsCompared with controls, individuals with AED exhibited significantly higher WBC levels (5.97 ± 1.13 vs. 5.45 ± 0.90 × 109/L; P < 0.05). NPAR values were markedly elevated in the AED group (16.31 [6.36]) relative to both VED (12.65 [5.57]) and controls (12.61 [7.05]) (P < 0.001). In the fully adjusted multivariate model, NPAR remained independently associated with AED (OR = 1.258; 95% CI: 1.159–1.362; P < 0.001), as did WBC (OR = 1.984; P < 0.001). ROC analysis revealed that NPAR had the greatest discriminative ability among all hematologic markers (AUC = 0.742; 95% CI: 0.676–0.809), with an optimal cut-off of 15.046 (sensitivity = 0.652; specificity = 0.753), outperforming WBC, NP, albumin, C-reactive protein (CRP), and neutrophils/lymphocytes ratio (NLR).ConclusionsElevated NPAR levels were significantly associated with AED. Compared with WBC and its individual components, NPAR exhibited superior discriminative ability for identifying AED. These findings suggest that NPAR may serve as a convenient and cost-effective hematologic parameter for assessing vascular risk in men with ED, although prospective studies are needed to validate this association.